An exploration of First Nations reserves and access to cash - Heng Chen; Walter Engert; Kim P. Huynh; Daneal O'Habib (Bank of Canada, 2021)
Providing bank notes is one of the Bank of Canada's core functions. The Bank is therefore interested in whether cash is adequately distributed across society, and this also influences the Bank's thinking on issuing a central bank digital currency. We provide a perspective on these issues by exploring access of First Nations reserves to cash. To do so, we measure the distance between the 637 reserve band offices in Canada and their closest cash sources. In this study, these cash sources are branches of financial institutions (FIs), automated bank machines (ABMs) owned by FIs, and white label ABMs. We measure the distance between band offices and cash sources by geographical distance ('as the crow flies') and by travel distance (e.g., road routes). We also provide some information on access to financial services more generally and set out questions for future research.
Keywords: E; E4; E41; E42; E5; G21; 330; Bank notes; Digital currencies and fintech; Financial institutions; Financial services; Payment clearing and settlement systems